Epidemiology of seasonal influenza in Bangkok between 2009 and 2012 - Prachayangprecha, Slinporn; Makkoch, Jarika; Suwannakarn, Kamol; Vichaiwattana, Preeyaporn; Korkong, Sumeth; Theamboonlers, Apiradee; Poovorawan, Yong (The Journal of Infection in Developing Countries, 2013)
Introduction: This study investigated influenza activity in Bangkok, Thailand between June 2009 and July 2012. Methodology: Real-time reverse transcription polymerase chain reaction (RT-PCR) was performed to detect influenza viruses among patients with influenza-like illnesses. Results: Of the 6417 patients tested, influenza virus infection was detected in 42% (n = 2697) of the specimens. Influenza A pH1N1 viruses comprised the predominant strain between 2009 and 2010, and seasonal influenza (H3) had a high prevalence in 2011. Laboratory data showed a prevalence and seasonal pattern of influenza viruses. In 2009, influenza activity peaked in July, the rainy season. In 2010, influenza activity happened in two phases, with the initial one at the beginning of the year and another peak between June and August 2010, which again corresponded to the rainy period. Influenza activity was low for several consecutive weeks at the beginning of 2011, and high H3N2 activity was recorded during the rainy season between July and September 2011. However, from the beginning of 2012 through July 2012, pH1N1, influenza H3N2, and influenza B viruses continuously circulated at a very low level. Conclusion: The seasonal pattern of influenza activity in Thailand tended to peak during rainy season between July and September.